JARGONS USED BY MALE BALINESE DANCER AT SANGGAR SENI MANIK UTTARA SINGARAJA - I N. N, Yadnya; D. P., Ramendra; I.A.M.I, Utami (International Journal of Language and Literature, 2019)
This study aimed at analyzing forms, meaning, and function of jargons used by male Balinese dancer at Sanggar Seni Manik Uttara Singaraja. This study was conducted in descriptive qualitative method. the subject of this study were 2 dancers of Traditional Balinese Dance especially male dancer in Sanggar Seni Manik Uttara Singaraja. In this study, the methods of data collection were observation and interview. The result of this study represents there are 22 jargons used by male Balinese dancer at Sanggar Seni Manik Uttara Singaraja in which jargons were classified and investigated based on word formation processes and word class. There are 5 affixations, 5 nouns, 2 verbs, 7 compounding, 3 reduplications. The meaning of jargons was analyzed based on the context of male Balinese dancers? conversation, picture, and interview. Additionally, this study denotes there are three function of jargons used by male Balinese dancer, to make communication effectively, to show the identity of the dancer and the last is to build the solidarity among Balinese dancer.